Soil clay mineralogy of banana-cultivated soils in the Caribbean lowlands of Costa Rica - Arias, Fulvio (2009)
This study includes thecharacterization of the claymineralogy of banana soils from11 watersheds of the Caribbean alluvial lowlands, using RXdiffraction and dissolutionmethods. These results confirm the abundance of montmorrillonite, metahalloisite, vermiculite and plagioclases, together with small amounts of allophane, gibbsite and iron oxides like hematite, maghemite and magnetite. Chlorite was not detected but illite was found in some samples. The use of dissolution and estequiometric techniques allowed us to identify amorphous materials, probably allophane, in soil RE-16 in the Tortuguero river basin. Soils northwest of the watershed of rivers Vueltas, Silencio and Parismina, were dominated by metahalloisite and montmorrillonite; they were classified as Inceptisols with Andic properties (Andic Eutrudepts, Aquandic Endoaquepts), Dystric Inceptisols (Fluventic Dystrudepts) and Andisols (Typic Hapludands). Soils southwest of that watershed were dominated by montmo rrillonite, vermiculite and metahalloisite; they were classified as Eutric Inceptisols of alluvial origin (Fluventic Eutrudepts, Dystric Fluventic Eutrudepts, Fluvaquentic Eutrudepts, Fluven-tic Endoaquepts) and Inceptisols with drainage problems (Fluventic Endoaquepts, Fluvaquentic Epiaquepts). The montmorillonite, vermiculite and allophane are formed in the hillsides of the watershed (cordilleras Central and Talamanca) and later deposited in the lowlands by river floo-ding; metahalloisite is formed by transformation of halloisite and gibbsite developed from allophanic materials.